(untitled) (Baghdad Science Journal, 2025)
Copper and Zinc powders with different particle sizes were subjected to sieving of range (20-100?m) and He-Ne laser system to determine the particle size . 1wt% from each powders was blended carefully with 99wt% from Iraqi oil . Microscopic examination were carried for all samples to reveal the particle size distribution . XRF intensity measurements were conducted for all suspended samples , and the relation between XRF intensity and the particle size was found .